A cost and delay estimation of a suite of low-cost adaptive routers for hierarchical torus network - Rahman, M.M. Hafizur; Akhand, M. A. H (2012)
A Hierarchical Torus Network (HTN) is a 2D-torus network of multiple basic modules, in which the basic modules are 3D-torus networks that are hierarchically interconnected for higher-level networks. Three deadlock-free adaptive routing algorithms called link-selection, channel-selection, and a combination of link-selection and channel-selection was proposed for the efficient use of physical links and virtual channels of an HTN to improve dynamic communication performance. However, the cost and delay of those routers is not evaluated yet. In this paper, We present a conservative estimation of hardware cost and router delay for the proposed routing algorithms and compare it with the dimension order routing. The hardware costs for the proposed adaptive routing algorithms are exactly equal to those for dimension order routing. The only overhead imposed is nominal router delay for header selection.